PEMBERIAN POC DENGAN RENTANG WAKTU BERBEDA TERHADAP KELIMPAHAN Chlorella sp - Rosyadi; Agusnimar; Hisra Melati (DINAMIKA PERTANIAN, 2019)
This study aims to determine the effect of giving POC with different time ranges on abundance. The study was carried out for 18 days in the Microalgae Laboratory of the Fish Seed Institute of the Faculty of Agriculture, Riau Islamic University, Pekanbaru. The method used is a completely randomized design (CRD) with 5 treatments 3 replications, namely: P1 giving POC on day 5, P2 giving POC on day 6, P3 giving POC on day 7, P4 giving POC on day -8 and P5 administration of POC on the 9th day. From the results of the study, the highest density of Chlorella sp was found on P3 treatment with a total density of 9,833,333 cells/ml on the 5th day. The lowest average peak was in the treatment of P1 with 2,566,667 cells/ml on the 12th day. Water quality such as temperature ranged from 25 to 300 C and pH between 6.5-7.